Influence of MoO3 on the Structure of Lithium Aluminum Phosphate Glasses - SADDEEK, Yasser B.; ABO-NAF, S. M. (Archives of Acoustics, 2012)
IR spectroscopy, density and ultrasonic velocity measurements have been carried out for aluminumlithium phosphate glasses with and without MoO3. The observed changes in the FTIR spectra of theglasses were related to the modifier/former role of molybdenum ions. The results revealed that the densityincreases with increasing MoO3 content, which was attributed to the increase in the compactness andpacking of the glass network. The ultrasonic data were analyzed in terms of creation of new bonds of MoO3attached to phosphate units. The new bonds increased the average crosslink density and the number ofnetwork bonds per unit volume along with a strengthening of the different modes of vibrations which inits turn increased the ultrasonic velocity, the rigidity and hence the elastic moduli of the glasses.